\[\boxed{\text{1208\ (1208).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[n^{7} - n = n\left( n^{6} - 1 \right) =\]
\[= n\left( n^{3} - 1 \right)\left( n^{3} + 1 \right) =\]
\[= n(n - 1)(n + 1)\left( \left( n^{2} + 1 \right)^{2} - n^{2} \right),\]
\[n(n - 1)(n + 1) - три\ \]
\[последовательных\ числа,\ \]
\[тогда\ их\ произведение\ \]
\[делится\ на\ 6.\]
\[Если\ число\ не\ делится\ на\ 7\ \]
\[и\ остаток - 1;0;1,\ то\ \]
\[n(n - 1)(n + 1) - делится\ на\ 7\ \]
\[или\ \left( \left( n^{2} + 1 \right)^{2} - n^{2} \right) - делится\ \]
\[на\ 7,\ если\ остаток - 2;2,\]
\[то\ \left( n^{2} + 1 \right)^{2} - n^{2} =\]
\[= (4 + 1)^{2} - 4 = 25 - 4 = 21 -\]
\[делится\ на\ 7,если\ остаток -\]
\[3;3,\ то\ \left( n^{2} + 1 \right)^{2} - n^{2} =\]
\[= (9 + 1)^{2} - 9 = 100 - 9 =\]
\[= 91 - делится\ на\ 7,\ \]
\[следовательно,\ получаем\ \]
\[6 \cdot 7 = 42 - делится\ на\ 42.\ \]
\[\boxed{\text{1208.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (x - 8)^{2} - (x - 4)(x + 4) = 0\]
\[x^{2} - 16x + 64 - \left( x^{2} - 16 \right) = 0\]
\[x^{2} - 16x + 64 - x^{2} + 16 = 0\]
\[x^{2} - x^{2} - 16x = - 64 - 16\]
\[- 16x = - 80\]
\[x = 80\ :16\]
\[x = 5\]
\[Ответ:\ x = 5.\ \]
\[2)\ (4x - 5)(4x + 5) - (4x - 1)^{2} =\]
\[= 9 - 2x\]
\[16x^{2} - 25 - \left( 16x^{2} - 8x + 1 \right) =\]
\[= 9 - 2x\]
\[16x^{2} - 16x^{2} + 8x + 2x =\]
\[= 9 + 25 + 1\]
\[10x = 35\]
\[x = 35\ :10\]
\[x = 3,5\]
\[Ответ:\ x = 3,5.\ \]